Influence of exercise order on the number of repetitions in untrained teenagers. - Moraes, Eveline; Nobre, Marcelo Pontes; Maia, Marianna de Freitas; Salles, Belmiro de Freitas; Miranda, Humberto; Simão, Roberto (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Prescription of resistance training (RT) is increasing among teenagers, requiring further studies to investigate the effects on this population. Objective: To examine the different orders on exercises sequence and its influence on the number of repetitions in teenager. Methods: Participated in the study 12 voluntarily male teenagers (14.91 ± 0.79 years, 1.69 ± 8.61 cm, 62.24 ± 7.26 kg) without experience in RT. After 48 hours of the last session of 10 repetitions maximum (10RM) test, subjects performed one of the four sequences of exercises in a counterbalanced crossover design. Four different sequences were also performed with a interval of 48 hours. All sequences were three sets of each exercise with 10RM load, with two-minute intervals between sets and exercises. The order of exercises was the sequence 1: bench press (BP), pulldown (PD), machine shoulder press (SP), biceps curl (BC) and triceps (TR); Sequence 2: TR, BC, SP, PD and BP; the sequence 3: Leg press (LP), leg extension (LE) and leg curl (LC); Sequence 4: LC, LE and LP. Results: Significant differences were observed (p <0.05) in the total number of repetitions for the BP exercises, SP, BC and TR for the sequence of the upper limbs and for the lower limbs and the LP and LE exercises. Conclusion: The results suggest that the performance of the average number of repetitions for sessions conducted with RT intensity of 10RM in teenagers was influenced by the different kind of exercises in both upper and lower limbs.